2020
DOI: 10.3389/fmicb.2020.00876
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Relationship of Inclusion Bodies of a Multimeric Protein

Abstract: High level expression of recombinant proteins in bacteria often results in their aggregation into inclusion bodies. Formation of inclusion bodies poses a major bottleneck in high-throughput recovery of recombinant protein. These aggregates have amyloid-like nature and can retain biological activity. Here, effect of expression temperature on the quality of Escherichia coli asparaginase II (a tetrameric protein) inclusion bodies was evaluated. Asparaginase was expressed as inclusion bodies at different temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 52 publications
0
28
0
1
Order By: Relevance
“…Amyloid-like properties were seen in β-galactosidase IBs expressed in E. coli , which were shown to be biologically active ( Carrió et al, 2005 ). Another study carried out by Singh et al (2020) to characterize asparaginase IBs confirmed the high β-content as well as the catalytic activity of the amyloid-like aggregates. Furthermore, it was determined that temperature could modulate the levels of reported amyloid features ( Singh et al, 2020 ).…”
Section: The Unique Features Of Protein Inclusion Bodies In mentioning
confidence: 73%
See 4 more Smart Citations
“…Amyloid-like properties were seen in β-galactosidase IBs expressed in E. coli , which were shown to be biologically active ( Carrió et al, 2005 ). Another study carried out by Singh et al (2020) to characterize asparaginase IBs confirmed the high β-content as well as the catalytic activity of the amyloid-like aggregates. Furthermore, it was determined that temperature could modulate the levels of reported amyloid features ( Singh et al, 2020 ).…”
Section: The Unique Features Of Protein Inclusion Bodies In mentioning
confidence: 73%
“…Another study carried out by Singh et al (2020) to characterize asparaginase IBs confirmed the high β-content as well as the catalytic activity of the amyloid-like aggregates. Furthermore, it was determined that temperature could modulate the levels of reported amyloid features ( Singh et al, 2020 ). The parallel findings were reported in a similar study ( Žerovnik et al, 2007 ).…”
Section: The Unique Features Of Protein Inclusion Bodies In mentioning
confidence: 73%
See 3 more Smart Citations